PERANCANGAN GAME EDUKASI â€œSEMANGAT SI SEMUTâ€ SEBAGAI MEDIA UNTUK MENANAMKAN SEMANGAT GOTONG ROYONG PADA ANAK USIA DINI - Sugiyanto Sugiyanto Sugiyanto; Khamadi Khamadi Khamadi (Semantik, 2011)
Globalization and the influence of foreign culture has caused a tremendous effect on the culture that had been upheld by the nation, especially the traditional culture of mutual help. In a relatively short time has turned into the properties of selfish, individualistic and indifferent nature and no longer want to care about what happens in the environment.Game a technology-based visual communications media that much-loved community, especially by children. Age of children are of age to play. With their play to develop emotional, physical and cognitive growth. By playing them develop imagination, skill, independence, creativity, and ability bersosialisasi.Semut is one of the most social groups in the genus of insects and live as a community, called "colonies", which was organized extremely well. Their organization is so advanced that it can be said in this respect they have a civilization that is similar to the development of human civilization. The used method is Multimedia Development Life Cycle (MDLC), which consists of several stages, among others: Concept, Design, Material Collecting, Assembly , Testing, Packaging and Distribution. This method is used, because the objects used in this project consists of multimedia elements, namely: text, pictures / graphics, animation and audio. From some of the positive nature of the ants, will be an adventure game that will introduce the meaning of the spirit of mutual cooperation. Children are taught to use their sense of empathy when playing the character of the ants, when there are other ants who need assistance or when the characters need help. So that can foster a spirit to socialize, collaborate and work together.Keywords : game, adventure ,mutual cooperation, mdlc